Acute In Vivo Response to an Alternative Implant for Urogynecology. (17th July 2014) - Roman Regueros, Sabiniano; Albersen, Maarten; Manodoro, Stefano; Zia, Silvia; Osman, Nadir I.; Bullock, Anthony J.; Chapple, Christopher R.; Deprest, Jan; MacNeil, Sheila
Abstract : Purpose . To investigate in vivo the acute host response to an alternative implant designed for the treatment of stress urinary incontinence (SUI) and pelvic organ prolapse (POP). Methods . A biodegradable scaffold was produced from poly-L-lactic acid (PLA) using the electrospinning technique. Human and rat adipose-derived stem cells (ADSCs) were isolated and characterized by fluorescence-activated cell sorting and differentiation assays. PLA scaffolds were seeded and cultured for 2 weeks with human or rat ADSCs. Scaffolds with and without human or rat ADSCs were implanted subcutaneously on the abdominal wall of rats. After 3 and 7 days, 6 animals from each group were sacrificed. Sections from each sample were analyzed by Haematoxylin and Eosin staining, Sirius red staining, and immunohistochemistry for CD68, PECAM-1, and collagen I and III. Results . Animals responded to the scaffolds with an acute macrophage response. After 7 days of implantation, there was extensive host cell penetration, new blood vessel formation, and new collagen deposition throughout the full thickness of the samples without obvious differences between cell-containing and cell-free scaffolds. Conclusions . The acute in vivo response to an alternative implant (both with and without cells) for the treatment of SUI and POP showed good acute integration into the host tissues.